PERBEDAAN KEMAMPUAN MOTORIK KASAR ANAK USIA 4-5 TAHUN YANG MENGIKUTI PEMBELAJARAN RENANG DENGAN YANG TIDAK MENGIKUTI PEMBELAJARAN RENANG DI TK SE-KECAMATAN LIMA PULUH KOTA PEKANBARU - Saragih, Serlina; Novianti, Ria; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research purposed is to know differences in gross motor skills of children aged 4-5 years who follow swimming exercise with children who do not follow the learning pool in kindergarten in the District of Lima Puluh Pekanbaru City. This research is a comparative research through observation sheet to the gross motor skills of children aged 4-5 years in kindergarten in the District of Lima Puluh Pekanbaru City. The sample used in this research 39 people. The data collection technique used is observation. Technique of data analysis using t-test test by using program of SPSS 16.0. Based on hypothesis test result obtained t count equal to 6,799. This shows that there is a difference between gross motor skills of children aged 4-5 years who follow swimming exercise with those who do not follow the swimming exercise. If there is any difference between t test and t test table then Ha is accepted and H0 is rejected. To prove the difference between the development of gross motor skills of children aged 4-5 years who follow swimming exercise activities with those who do not follow the swimming learning can be tested